Exploiting the advantages of a wireless seed localization system that differentiates between the seeds: Breast cancer resection following neoadjuvant chemotherapy. Issue 1 (8th August 2022) - Shaughnessy, Elizabeth; Vijapura, Charmi; Reyna, Chantal; Lewis, Jaime; Lewis, Kyle; Lee, Su‐Ju; Sobel, Lawrence; Wahab, Rifat; Rosen, Lauren; Brown, Ann
Abstract: Background: Most wireless localization methods utilize only one means of detection for the surgeon, sufficient to localize a single small breast lesion for excision. Complex cases requiring bracketing of a larger lesion or localization of two or more close lesions can superimpose the signal from separate "seeds" with such methods. The lack of discernment between the localization "seeds" can disorient the surgeon, risking a missed lesion on excision and longer operative times. with the use of neoadjuvant chemotherapy prior to breast surgery, the necessity of localizing both a breast lesion and an axillary lymph node previously biopsied is becoming frequent. Case: A 44 year‐old woman underwent neoadjuvant chmotherapy for a breast cancer the did not express estrogen receptor, progesterone receptor, or HER2 receptor. In establishing the extent of disease, a suspicious ipsilateral lymph node was biopsied and found to contain metastatic disease. She had an excellent response to the chemotherapy, with decreased size of the primary tumor and the previously biopsied lymph node. The patient desired breast conservation. The primary tumor and associated calcifications were bracketed using two different Smartclips™, with a third localizing the lymph node biopsied. Conclusion: This report illustrates how the use of three SmartClips™, within the EnVisioTM system, allowed for separate tracking of each "seed" throughout a complex surgery in a patient following neoadjuvant chemotherapy. This resulted in successful resection of both the tumor and the tagged lymph node.